Zones of influence for soil organic matter dynamics: A conceptual framework for data and models. (28th August 2019) - Cagnarini, Claudia; Blyth, Eleanor; Emmett, Bridget A.; Evans, Chris D.; Griffiths, Robert I.; Keith, Aidan; Jones, Laurence; Lebron, Inma; McNamara, Niall P.; Puissant, Jeremy; Reinsch, Sabine; Robinson, David A.; et al.
Abstract: Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an 'intrinsic property' to SOM persistence as an 'ecosystem interaction'. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring. Abstract : A new conceptual framework is proposed to improve our understanding of soil organic matter behaviour at depth: at any soil profile, two vertically distinct, dynamic zones of influence can be identified, an upper vegetation zone of influence (VZI), controlled by plant traits, and a lower mineral matrix zone of influence (MMZI), controlled by geochemical interactions. In the VZI, soil organic carbon (SOC) flux is upwards to the atmosphere (SOC mineralization to CO2 ), while in the MMZI, the SOC flux is downwards to deep soil storage (SOC stabilization and persistence), as it is suggested by SOC profiles in analogy to the 'zero‐flux plane' concept in hydrology.